Penerapan algoritma proses asuhan gizi terstandar berbasis skrining gizi - Susetyowati Susetyowati; Hamam Hadi; Ahmad Husein Asdie; Mohammad Hakimi (Jurnal Gizi Klinik Indonesia, 2014)
Background: Malnutrition is one common problem for hospitalized patient, estimated between 20-60%. American Dietetic Association (ADA) recommends a standardized Nutrition Care Process (SNCP) that ensures services and outcomes in the quality management of nutrition care to all patients based on an individual basis and scientific facts. In Indonesia was developed nutrition screening tool, namely the Simple Nutrition Screening Tool (SNST) which was valid and reliable.Objective: The study was to determine the effect of SNCP based on screening to improve nutrient intake and nutritional status.Method: The method using a 2x2 factorial design, with 4 groups which are: screened with Nutritional Risk Screening (NRS) and get hospital-based SNCP (A1B1); screened with NRS and algorithm SNCP (A1B2); screened with SNST and get hospital-based SNCP (A2B1); screened with the SNST and get algorithm SNCP (A2B2).Results: Nutritional screening interventions using NRS and SNST method can increase the energy and protein intake also Mid-Upper Arm Circumference (MUAC). There is no relationship between algorithm SNCP with nutrient intake and nutritional status, although the average intake of energy, protein, MUAC and albumin was better in the algorithm SNCP than in hospital-based SNCP. The interaction between the SNST and algorithm SNCP have better mean intake of energy, protein and MUAC changes than other groups. The size of the effect of energy intake, protein intake, and MUAC was 129 kcal; 4.6 g; and 0.35 cm, respectively.Conclusion: Interaction between an SNST and algorithm SNCP have a better average intake of energy, protein, and MUAC compared with other groups.